Serious Games: A new Approach to Foster Information and Practices About Covid-19? - Montalbano, L.; Gallo, L.; Ferrante, G.; Malizia, V.; Cilluffo, G.; Fasola, S.; Alesi, M.; La Grutta, S. (Frontiers in Robotics and AI, 2022)
The current Covid-19 pandemic poses an unprecedented global challenge in the field of education and training. As we have seen, the lack of proper information about the virus and its transmission has forced the general population and healthcare workers to rapidly acquire knowledge and learn new practices. Clearly, a well-informed population is more likely to adopt the correct precautionary measures, thus reducing the transmission of the infection; likewise, properly educated healthcare workers are better equipped to manage the emergency. However, the need to maintain physical distancing has made it impossible to provide in-presence information and training. In this regard, new technologies have proved to be an invaluable resource by facilitating distance learning. Indeed, e-learning offers significant advantages because it does not require the physical presence of learners and teachers. This innovative method applied to serious games has been considered potentially effective in enabling rapid and large-scale dissemination of information and learning through content interactivity. We will review studies that have observed the development and use of serious games to foster information and practices about Covid-19 aimed at promoting behavioral changes in the population and the healthcare personnel involved on the front line.